High-performance, flexible electronic skin sensor incorporating natural microcapsule actuators. (June 2017) - Wang, Lili; Jackman, Joshua A.; Tan, Ee-Lin; Park, Jae Hyeon; Potroz, Michael G.; Hwang, Ee Taek; Cho, Nam-Joon
Abstract: The incorporation of stimuli-responsive elastic components within wearable sensors holds excellent potential for reinforcing structural features as well as improving high-performance detection capabilities. Herein, we report the development of a highly sensitive electronic skin (e-skin) sensor that is based on incorporating natural, elastic microcapsules within a biomimetic architecture, and this design represents a new biologically-inspired approach to design wearable sensors. Configured as a pressure sensor, the device exhibited the lowest reported limit of detection for applied pressure (1.6 Pa) and discriminated between multiple spatiotemporal tactile stimuli under both static and dynamic pressure conditions. Furthermore, the device displayed high stability over 25, 000 cycles and inclusion of the natural microcapsules imparted hydrophobic character that facilitated waterproofing for all-weather use. This work opens new directions for incorporating stimuli-responsive microcapsules into e-skin sensor designs as well as highlights the potential of utilizing natural biomaterials to improve the performance and functionality of bioelectronic devices. Graphical abstract: A biocompatible and waterproof biomimetic electronic skin sensor was fabricated based on an interlocked 3D matrix rubber with natural microcapsules. The functionalized natural microcapsules were rationally engineered and loaded into a conductive material with excellent hydrophobicity and toughness. The sensor surface exhibited high-performance sensor capabilities for the precise perception of multiple spatiotemporal tactile stimuli and was durable amidst water exposure. Highlights: Natural microcapsules provide a highly sensitive actuating element for e-skin sensors and wearable electronics. 3D composite architecture enables excellent durability and ultrahigh sensitivity. Human physiological signals can be monitored in real-time. Device enables precise mapping of spatiotemporal pressure distribution.